IGF2BP2 promotes head and neck squamous carcinoma cell proliferation and growth via the miR-98-5p/PI3K/Akt signaling pathway - Yu, Dan; Xiao, Zhenlong; Zou, Zhefei; Lin, Ling; Li, Jing; Tan, Jian; Chen, Wei (Frontiers in Oncology, 2023)
Introduction As a N6-methyladenosine reader protein, Insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2) is a critical player in tumor progression and metastasis. However, its specific function in head and neck squamous carcinoma (HNSCC) has yet to be determined. The present study aimed to determine the role of IGF2BP2 in HNSCC. Methods The expression of IGF2BP2 in HNSCC was analyzed using The Cancer Genome Atlas (TCGA) dataset and detected in HNSCC tissues and cells, respectively. Gain- and loss- of function methods were employed to study the effects of IGF2BP2 on HNSCC cell proliferation and tumorigenesis in vitro and in vivo. MicroRNAs (miRNAs) regulating IGF2BP2 were predicted using online tools and confirmed experimentally. Results We showed augmented IGF2BP2 expression in HNSCC, which correlated with poor clinical outcomes. Functional studies showed that IGF2BP2 promoted HNSCC cell proliferation by facilitating cell cycle progression while inhibiting apoptosis. We further demonstrated that IGF2BP2 could enhance HNSCC cell tumorigenesis in vivo. Mechanistically, our data revealed that miR-98-5p could directly target IGF2BP2. The interplay between IGF2BP2 and miR-98-5p is essential to drive the progression of HNSCC via the phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)-protein kinase B (Akt) pathway signaling pathway. Discussion The current study revealed the oncogenic role of IGF2BP2 and provided insights into its potential mechanism in HNSCC tumorigenesis. Additionally, IGF2BP2 might represent a promising therapeutic target and serve as prognostic biomarker in patients with HNSCC.